Using Language Sampling in Clinical Assessments with Bilingual Children: Challenges and Future Directions - Gutiérrez-Clellen, Vera F. (2009)
Current language tests designed to assess Spanish-English-speaking children have limited clinical accuracy and do not provide sufficient information to plan language intervention. In contrast, spontaneous language samples obtained in the two languages can help identify language impairment with higher accuracy. In this article, we describe several diagnostic indicators that can be used in language assessments based on spontaneous language samples. First, based on previous research with monolingual and bilingual English speakers, we show that a verb morphology composite measure in combination with a measure of mean length of utterance (MLU) can provide valuable diagnostic information for English development in bilingual children. Dialectal considerations are discussed. Second, we discuss the available research with bilingual Spanish speakers and show a series of procedures to be used for the analysis of Spanish samples: (a) limited MLU and proportional use of ungrammatical utterances; (b) limited grammatical accuracy on articles, verbs, and clitic pronouns; and (c) limited MLU, omission of theme arguments, and limited use of ditransitive verbs. Third, we illustrate the analysis of verb argument structure using a rubric as an assessment tool. Estimated scores on morphological and syntactic measures are expected to increase the sensitivity of clinical assessments with young bilingual children. Further research using other measures of language will be needed for older school-age children.